2022
DOI: 10.22441/sinergi.2022.1.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of 3D, 4D, and 5D Building Information Modeling for reducing claims to service providers

Abstract: In construction, claims are usually a request for additional time, cost, or quality of work. A dispute will occur If the claim is not resolved correctly. In industrial revolution 4.0, we can use the Building Information Modeling (BIM) method to increase efficiency. BIM is a digital display containing all information about building elements integrated with the building's life cycle period. BIM will accelerate and reduce risks in construction, including the impact of claims. In Indonesia, several consultants/con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…The use of 3D, 4D, and 5D BIM in construction today is extremely beneficial to consultants/contractors in terms of reducing claims to service providers. Previous research by the researchers have revealed relevant findings (Noviani et al, 2022;J. C. P. Cheng et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…The use of 3D, 4D, and 5D BIM in construction today is extremely beneficial to consultants/contractors in terms of reducing claims to service providers. Previous research by the researchers have revealed relevant findings (Noviani et al, 2022;J. C. P. Cheng et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Building owners, especially the government, feel allergic to the term claim while contractors feel reluctant to file claims for fear of being recorded as fussy or demanding contractors. Service providers who often submit claims are usually not given recommendations or included in the next tender opportunity (Noviani, Amin, & Hardjomuljadi, 2022). Some construction service companies look for opportunities to win tenders no longer in efficiency but from accuracy when seeing large claim opportunities at tender time (Harto et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…BIM may improve information efficiency and availability by integrating information from all construction activities throughout a project, which benefits stakeholders [26]. Therefore, implementing BIM 5D can minimize service provider complaints [27]. The BIM 5D is majorly established on the elements of an information model that can be implemented throughout the life cycle of a building to present accurate financial data.…”
Section: Introductionmentioning
confidence: 99%